High resistance of transgenic cabbage plants with a synthetic cry1Ia8 gene from Bacillus thuringiensis against two lepidopteran species under field conditions. Issue 2 (8th April 2015) - Yi, Dengxia; Yang, Weijie; Tang, Jun; Wang, Li; Fang, Zhiyuan; Liu, Yumei; Zhuang, Mu; Zhang, Yangyong; Yang, Limei
Abstract: BACKGROUND: Plutella xylostella (Linnaeus) has become the most destructive pest in cabbage throughout the world. Cry1Ia8 cabbage has been developed to reduce pest attacks. To gain a better understanding of the efficacy of Cry1Ia8 cabbage, a homozygous Cry1Ia8 cabbage line A14‐5 was produced, and its resistance to P. xylostella, Pieris rapae (Linnaeus) and other lepidopteran pests was evaluated in the field in 2011, 2012 and 2013. RESULTS: Under natural infestation conditions, the homozygous transgenic line was highly resistant against P. xylostella and P. rapae as compared with the untransformed control and susceptible to Mamestra brassicae (Linnaeus) and Spodoptera exigua (Hübner). The homozygous transgenic plants showed slight symptoms of damaged leaves by lepidopteran species, while the untransformed plants exhibited serious damage symptoms throughout the cabbage growing season. CONCLUSION: Compared with the control, the homozygous transgenic cabbage line showed great potential for protecting cabbage from attack by P. xylostella and P. rapae in the field. © 2015 Society of Chemical Industry